448. Disproportionate Burden of COVID-19 on Latinx Residents among Hospitalized Patients at San Francisco's Public Health Hospital. (31st December 2020) - Jain, Vivek; Brown, Lillian B; Marquez, Carina; Rubio, Luis; Spottiswoode, Natasha; Churnet, Bethlehem; Brooks, Katherine; Zhou, Mengyu; Muldoon, Timothy; Hendrickson, Carolyn; Cattamanchi, Adithya; Gomez, Antonio; et al.
Abstract: Background: San Francisco implemented one of the earliest shelter-in-place public health mandates in the U.S., with flattened curves of diagnoses and deaths. We describe demographics, clinical features and outcomes of COVID-19 patients admitted to a public health hospital in a high population-density city with an early containment response. Methods: We analyzed inpatients with COVID-19 admitted to San Francisco General Hospital (SFGH) from 3/5/2020–5/11/2020. SFGH serves a network of >63, 000 patients (32% Latinx/24% Asian/19% African American/19% Caucasian). Demographic and clinical data through 5/18/2020 were abstracted from hospital records, along with ICU and ventilator utilization, lengths of stay, and in-hospital deaths. Results: Of 157 admitted patients, 105/157 (67%) were male, median age was 49 (range 19-96y), and 127/157 (81%) of patients with COVID-19 were Latinx. Crowded living conditions were common: 60/157 (38%) lived in multi-family shared housing, 12/1578 (8%) with multigenerational families, and 8/157 (5%) were homeless living in shelters. Of 102 patients with ascertained occupations, most had frontline essential jobs: 23% food service, 14% construction/home maintenance, and 10% cleaning. Overall, 86/157 (55%) of patients lived in neighborhoods home to majority Latinx and African-American populations. Overall, 45/157 (29%) of patients needed ICU care, and 26/157 (17%) required mechanical ventilation; 20/26 (77%) of ventilated patients were successfully extubated, and 137/157 (87%) were discharged home. Median hospitalization duration was 4 days (IQR, 2–10), and only 6/157 (4%) patients died in hospital. Conclusion: In San Francisco, where early COVID-19 mitigation was enacted, we report a stark, disproportionate COVID-19 burden on Latinx patients, who accounted for 81% of hospitalizations despite making up only 32% of the patient base and 15% of San Francisco's total population. Latinx inpatients frequently lived in high-density settings, increasing household risk, and frequently worked essential jobs, potentially limiting the opportunity to effectively distance from others. We also report here favorable clinical outcomes and low overall mortality. However, an effective COVID-19 response must urgently address racial and ethnic disparities. Disclosures: All Authors : No reported disclosures